Involvement of G-protein beta gamma subunits on the influence of inhibitory alpha(2)-autoreceptors on the angiotensin AT(1)-receptor modulation of noradrenaline release in the rat vas deferens - Carlos Talaia (2006)
The influence of alpha(2)-autoreceptors on the facilitation of [H-3]-noradrenaline release mediated by angiotensin R was studied in prostatic portions of rat vas deferens preincubated with [H-3]-noradrenatine. Angiotensin II enhanced tritium overflow evoked by trains of 100 pulses at 8 Hz, an effect that was attenuated by the AT(1)-receptor antagonist losartan (0.3-1 mu M), at concentrations suggesting the involvement of the AT(1B) subtype. The effect of angiotensin II was also attenuated by inhibition of phospholipase C (PLC) and protein kinase C (PKC) indicating that prejunctional AT(1)-receptors are coupled to the PLC-PKC pathway. Angiotensin II (0.3-100 nM) enhanced tritium overflow more markedly, up to 64%, under conditions that favor alpha(2)-autoinhibition, observed when stimulation consisted of 100 pulses at 8 Hz, than under poor alpha(2)-autoinhibition conditions, only up to 14%, observed when alpha(2)-adrenoceptors were blocked with yohimbine (1 mu M) or when stimulation consisted of 20 pulses at 50 Hz. Activation of PKC with 12-myristate 13-acetate (PMA, 0.1-3 mu M) also enhanced tritium overflow more markedly under strong alpha(2)-autoinhibition conditions. Inhibition of G(i/o)-proteins with pertussis toxin (8 mu g/ml) or blockade of G beta gamma subunits with the anti-beta gamma peptide MPS-Phos (30 mu M) attenuated the effects of angiotensin II and PMA. The results indicate that activation of AT(1)-receptors coupled to the PLC-PKC pathway enhances noradrenaline release, an effect that is markedly favoured by an ongoing activation of alpha(2)-autoreceptors. Interaction between alpha(2)-adrenoceptors and AT(1)-receptors seems to involve the beta gamma subunits released from the G(i/o)-proteins coupled to alpha(2)-adrenoceptors and protein kinase C activated by AT(1)-receptors.